Pengaruh Persepsi Karir dan Motivasi Terhadap Minat Berkarir di Bidang perpajakan Dengan Pemahaman Tri Pantangan Sebagai Variabel Moderasi - Ayem, Sri; Putra Setiawan, Syaifu Rizal (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to examine the effect of career perceptions and motivation on interest in a career in the field of taxation with an understanding of the Three Abstinences as a moderating variable in students of the Yogyakarta Private College Accounting Study Program. The technique used in taking the sample was a purposive sampling technique, namely 5 private tertiary institutions in Yogyakarta in 2019-2020 with a total population of 1320 students and a research sample of 100 students was taken from the slovin formula. The data used in this research is primary data in the form of questionnaires. The data analysis technique used in this study is Moderated Regression Analysis (MRA). The results showed that the influence of career perceptions and motivation had a positive effect on interest in a career in the field of taxation, understanding of the Three taboos could not strengthen career perceptions and motivation on a career interest in taxation. The implications of this research are expected to influence the interest of accounting students to have a career in the field of taxation by practicing the teachings of Ki Hajar Dewantara, one of which is the Tri taboo teaching, namely not to abuse the power or authority they have.